Ecological gabions for flood protection and biotic balance in the Chacarilla town of the Matagente river - Custodio Salas, Manuel Alejandro (2024)
River flooding continually threatens safety, infrastructure and health in urban environments and the environment, generating significant risks for communities. The objective of this article is to carry out the sizing of ecological gabion walls for flood protection and biotic balance in the Chacarilla town of the Matagente River. The methodology used was multidisciplinary from basic, specific and detailed studies. Empirical and numerical methods will be applied for hydrological and hydraulic conditions, as well as mathematical models for the sizing of the ecological gabion wall. The Leopold matrix was applied with a qualitative and quantitative approach for the analysis of environmental impact. For the processing and analysis of the information, different calculation tools were used such as ArcGIS Pro 2.0, HEC HMS, Hec Ras and Gawac 3.0. As the main results, the maximum flow was achieved first, which was 1379.63 m3/s for a return period of 140 years, which generated a maximum scour of 5.3 m along +0.000m to +880.00m of the river section. Therefore, the dimensions of the ecological gabion wall were 8 m high, 4.5 m wide for a total of 14960 blocks. A budget for the work was estimated at S/.6,699,633.85. As conclusions, it is defined that ecological gabion walls are a viable alternative to mitigate floods and care for the environment.